A Performance Competence-based Needs Assessment of Missouri School-based Agricultural Educators in Agricultural Mechanics Laboratory Management - Saucier, P. Ryan; McKim, Billy R.; Terry, Jr., Rob; Schumacher, Leon G. (Journal of Agricultural Systems, Technology, and Management, 2014)
This study investigated the laboratory management in-service needs of Missouri agriculture teachers who were responsible for managing agricultural mechanics laboratories. Teachers’ performance competence was assessed using the Borich (1980) needs assessment model to determine the in-service needs of these teachers. Researchers found that teachers were in need of in-service education in numerous areas of laboratory management; however, the most needed areas regarded the handling, storage, and disposing of hazardous materials, administering first aid, and correcting hazardous conditions. Results indicated teacher educators and state supervisory staff should provide continuing education for teachers in the area of laboratory management through technical workshops, summer conferences, and university instructed graduate level courses.